Estrogen receptor β upregulates CCL2 via NF-κB signaling in endometriotic stromal cells and recruits macrophages to promote the pathogenesis of endometriosis. Issue 4 (6th March 2019) - Gou, Yanling; Li, Xue; Li, Peiling; Zhang, Hongyan; Xu, Tenghan; Wang, Hao; Wang, Beidi; Ma, Xuesong; Jiang, Xue; Zhang, Zongfeng
Abstract: STUDY QUESTION: How is the activation of estrogen receptor β (ERβ) in endometriotic stromal cells (ESCs) involved in macrophage recruitment to promote the pathogenesis of endometriosis? SUMMARY ANSWER: ERβ modulates the production of C-C motif chemokine ligand 2 (CCL2) via nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling in ESCs and thus recruits macrophages to ectopic lesions to promote pathogenesis. WHAT IS KNOWN ALREADY: Macrophages are mainly recruited to the peritoneal cavity to promote the pathogenesis of endometriosis. Recent studies have demonstrated that ERβ plays an important role in the progression of endometriosis through modulating apoptosis and inflammation. STUDY DESIGN, SIZE, DURATION: An observational study consisting of 22 cases (women with endometriosis, diagnosed by laparoscopy and histological analysis) and 14 controls (without endometriosis) was carried out. PARTICIPANTS/MATERIALS, SETTING, METHODS: Tissues and stromal cells that were isolated from 22 patients with ovarian endometrioma and deeply infiltrating endometriosis were compared with tissues and stromal cells from 14 patients with normal cycling endometrium using immunohistochemistry, quantitative PCR, Western blot, cell migration assay and cloning formation assay. P values < 0.05 were considered significant, and experiments were repeated in at least three different cell preparations. MAIN RESULTS AND THE ROLE OF CHANCE: We observed that accumulated macrophages were recruited to the ectopic milieu and mainly adopted an alternatively activated macrophage (M2) phenotype. To reveal the underlying mechanism for this, we conducted a series of experiments and found that high expression of ERβ led to the production of CCL2 via NF-κB signaling and macrophages were recruited to the ectopic milieu. An in vitro co-culture assay also suggested that the recruited macrophages in turn could promote the proliferation and clonogenic ability of ESCs. Overall, the activation of ERβ in ESCs is involved in macrophage recruitment via NF-κB/CCL2 signaling and subsequently appears to promote the pathogenesis of endometriosis. LARGE SCALE DATA: N/A. LIMITATIONS, REASONS FOR CAUTION: Due to the limitations of obtaining surgical specimens, endometrioma tissues were collected mainly from women diagnosed with middle to late stage endometriosis. We identified the predominant presence of M2 macrophages in the samples used in our study, but the underlying mechanism of how recruited macrophages acquire the M2 phenotype is undefined. WIDER IMPLICATIONS OF THE FINDINGS: This work provides novel insight into the mechanism by which ERβ may modulate macrophage infiltration and promote pathogenesis, which may provide a new therapeutic target for endometriosis. STUDY FUNDING/COMPETING INTEREST(S): This study was supported by the National Natural Science Foundation of China (81671430). The authors have no conflicts of interest.